2009
DOI: 10.1128/aac.00180-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Aztreonam and Ceftazidime Pharmacodynamics with Escherichia coli in Combination with Daptomycin, Linezolid, or Vancomycin in an In Vitro Pharmacodynamic Model

Abstract: In an in vitro pharmacodynamic model, linezolid attenuated the activity of aztreonam and ceftazidime against Escherichia coli. Conversely, synergy was detected at 24 and 48 h when daptomycin or vancomycin was added to aztreonam and ceftazidime. We conclude that significant yet underappreciated interactions may occur between gram-positive-spectrum and gram-negative-spectrum antibacterials. Chicago, IL, 2007). Linezolid demonstrates minimal activity against gram-negative bacteria, so an explanation for worse ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Consistent with previous in vitro checkerboard studies (6,11,20), there was no evidence of in vivo antagonism or synergy of the combination of linezolid and ciprofloxacin. These findings are of particular interest given the recent phase 3 comparison of linezolid and vancomycin in patients with complicated skin and skin structure infections and catheter-related bloodstream infections due to Gram-positive pathogens, in which a mortality imbalance was reported for the linezolid arm (22).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with previous in vitro checkerboard studies (6,11,20), there was no evidence of in vivo antagonism or synergy of the combination of linezolid and ciprofloxacin. These findings are of particular interest given the recent phase 3 comparison of linezolid and vancomycin in patients with complicated skin and skin structure infections and catheter-related bloodstream infections due to Gram-positive pathogens, in which a mortality imbalance was reported for the linezolid arm (22).…”
Section: Discussionsupporting
confidence: 78%
“…Although the FIC index derived using the checkerboard technique is both popular and simple to obtain (15), it has several well-documented limitations (9). A more recent in vitro study of linezolid, daptomycin, and vancomycin suggested there was some attenuation of activity against Escherichia coli ATCC 25922 when linezolid was used in combination with ceftazidime or aztreonam at 48 h in an in vitro pharmacodynamic model (IVPM) system (11). However, in a separate study, no antagonism was observed in an IVPM system using linezolid in combination with aztreonam or ceftazidime at clinically relevant concentrations against the same E. coli strain (6).…”
Section: Discussionmentioning
confidence: 99%
“…Time-kill studies (TKS) were performed on all five CREC strains with amikacin, aztreonam, cefepime, doripenem, imipenem, levofloxacin, meropenem, piperacillin-tazobactam, rifampin, and tigecycline singly and in two-antibiotic combinations with polymyxin B. The antibiotic concentrations used were based on maximal clinically relevant unbound concentrations when maximum antibiotic doses were administered and are shown in Table 5 (13,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The procedures for the TKS have been described in detail in our previous study (10).…”
Section: Methodsmentioning
confidence: 99%
“…To date, there have been limited investigations of daptomycin and linezolid in combination (5, 6). The combined use of these agents prompted an investigation into pharmacokinetic and pharmacodynamic activity and possible interactions when using combinations of bactericidal and bacteriostatic antimicrobials as previously described (7,8).(A portion of these results were presented as a poster at the 53rd annual Interscience Conference on Antimicrobial Agents and Chemotherapy [ICAAC], Denver, CO, 10 September 2013.) Two randomly selected clinical MRSA blood isolates (L31 and L328) from the LaPlante Laboratory at the Providence Veterans Affairs Medical Center were selected for analysis.…”
mentioning
confidence: 99%